Analysis Of The Structure And Components Of Financial Reports Of Sharia Financial Institutions - Anita Dwi Utami (LPPM Universitas Sebelas April, 2023)
One of the sharia financial institutions that can provide financing to the community is the Sharia People's Credit Agency. The existence of Sharia People's Credit Agency has a specific objective, namely providing banking services and products for economically weak communities and small and micro businesses (SMEs) both in urban and rural areas. BPRS Harta Insan Karimah Cibitung (BPRS HIK Cibitung) is a People's Credit Agency which operates in the sharia sector using PSAK Syariah and PSAK ETAP. Sharia Financial Institutions exist as an alternative for Muslims for those who need capital and other financing to be free from gharar, maisir and usury. The components of financial statements according to PSAK 101 are 7 components. The research method used is descriptive analysis with the research object BPRS HIK Cibitung. Data analysis carried out in this research was through data reduction, data presentation and drawing conclusions. The research results show that the structure and components of financial report presentation at BPRS HIK Cibitung are in accordance with Sharia Financial Accounting Standards prepared by the Indonesian Accountants Association, namely PSAK 101 Concerning Financial Reports of Sharia Entities.